2020
DOI: 10.1021/acs.joc.0c02284
|View full text |Cite
|
Sign up to set email alerts
|

Formation of 3-Aminophenols from Cyclohexane-1,3-diones

Abstract: meta-Aminophenols are formed by the action of DBU on 3-amino-2-chlorocyclohex-2-en-1-ones at room temperature in MeCN. The chloro compounds are generated by treating 3-aminocyclohex-2-en-1-ones with the easily prepared halogenating agent BnNMe3·ICl2 in MeOH-CH2Cl2. The amino group must carry two substituents, either two aryl, one aryl and one alkyl, or two alkyl groups; 3-aminocyclohex-2-en-1-ones of this type are readily made from cyclohex-2-en-1-one and a primary or secondary amine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…According to the literature, 13b 1,3-cyclohexadione 6a (5.0 g, 39.7 mmol), methanol (8 mL, 198 According to the literature, 19 1,3-cyclohexadione 6a (100 mg, 0.89 mmol) was dissolved in AcOH (1 mL), and NH2Me (0.76 mL, 2M in THF, 1.52 mmol) was added. The reaction was sealed and stirred at 90 ℃ for 33 h. The solvent was evaporated, Flash chromatography of the residue over silica gel using DCM/MeOH (30:1, v/v) gave 6c (91 mg, 82%) as a yellow amorphous powder.…”
Section: -Methoxycyclohex-2-en-1-one (6b)mentioning
confidence: 99%
“…According to the literature, 13b 1,3-cyclohexadione 6a (5.0 g, 39.7 mmol), methanol (8 mL, 198 According to the literature, 19 1,3-cyclohexadione 6a (100 mg, 0.89 mmol) was dissolved in AcOH (1 mL), and NH2Me (0.76 mL, 2M in THF, 1.52 mmol) was added. The reaction was sealed and stirred at 90 ℃ for 33 h. The solvent was evaporated, Flash chromatography of the residue over silica gel using DCM/MeOH (30:1, v/v) gave 6c (91 mg, 82%) as a yellow amorphous powder.…”
Section: -Methoxycyclohex-2-en-1-one (6b)mentioning
confidence: 99%
“…Thus, the positive effect of AcOH as a solvent was confirmed. 13 Further experimentation revealed that the concentration of the reactant solution could be increased to 2.0 M from 0.2 M and the residence time could be shortened to 5 minutes from 30 minutes (Table 1, entry 10). 14 With this change, the processing rate of N -methylaniline ( 9 ) increased 60 times from 0.13 to 7.8 mL per hour.…”
Section: Resultsmentioning
confidence: 99%
“…3-Aminophenol (empirical formula C 6 H 7 NO, CAS No. 591–27–5, shown in Figure ) is a pharmaceutical intermediate . It is a white crystalline powder.…”
Section: Introductionmentioning
confidence: 99%
“…591− 27−5, shown in Figure 1) is a pharmaceutical intermediate. 1 It is a white crystalline powder. 3-Aminophenol, an intermediate, is widely used in pesticides, medicines, dyes, the petrochemistry industry, and other fields.…”
Section: Introductionmentioning
confidence: 99%